Photochemical CO2 Reduction Using Rhenium(I) Tricarbonyl Complexes with Bipyridyl‐Type Ligands with and without Second Coordination Sphere Effects. Issue 6 (28th May 2021) - Rotundo, Laura; Grills, David C.; Gobetto, Roberto; Priola, Emanuele; Nervi, Carlo; Polyansky, Dmitry E.; Fujita, Etsuko
Abstract: The front cover artwork is provided by Elena Amadio, University of Torino (Italy). The image shows the photocatalytic reduction of CO2 to CO by an aniline‐substituted Re‐bpy catalyst in the presence of a strong electron donor (BIH). Read the full text of the Article at 10.1002/cptc.2020000307 . Abstract : "We investigated the effect of different substituents on the 2, 2′‐bipyridine backbone, including PhOH and PhNH2 groups, during photochemical CO2 reduction with tricarbonyl Re complexes in order to understand the structure–function relationship and to compare the catalytic activity with previously published electrochemical results…." This and more about the story behind the front cover can be found in the Article at 10.1002/cptc.202000307 .